Resposta :
Resposta:
a) N=2.(+7)+5.(-2)
N=+14+(-10)
N=+14-10
N=+4
b) N=(-6).(-3)+2.(-6)
N=+18+(-12)
N=+18-12
N=-6
c) N=3.(+8)-7.(-7)
N=+24-(-49)
N=+24+49
N=+73
d) N=2·(+10)+5.(-2)-10
N=+20+(-10)-10
N=+20-10-10
N=+20-20
N=0
e) N=3.(-1)-5.(-1)+4.(-1)
N=-3-(-5)+(-4)
N=-3+5-4
N=5-7
N=-2
f) N=10-(-1)+(-1).(+3)-2.(+3)+2
N=10+1+(-3)-(+6)+2
N=10+1-3-6+2
N=11-9+2
N=+2+2
N=+4
g) N=-4+(-1)-(+5).(-3)-4+7.(-2)
N=-4-1-(-15)-4+(-14)
N=-5+15-4-14
N=+10-18
N=-8
h) N=8.(-5)-(-7).(+2)-3-4.(-1)+6
N=-40-(-14)-3-(-4)+6
N=-40+14-3+4+6
N=-26-3+10
M=-29+10
N=-19